2014
DOI: 10.4279/pip.060009
|View full text |Cite
|
Sign up to set email alerts
|

Granular discharge rate for submerged hoppers

Abstract: The discharge of spherical grains from a hole in the bottom of a right circular cylinder is measured with the entire system underwater. We find that the discharge rate depends on filling height, in contrast to the well-known case of dry non-cohesive grains. It is further surprising that the rate increases up to about twenty five percent, as the hopper empties and the granular pressure head decreases. For deep filling, where the discharge rate is constant, we measure the behavior as a function of both grain and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
47
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 34 publications
7
47
1
Order By: Relevance
“…In both dry and submerged cases, the grain volume fraction is measured to be φ = 0.58 ± 0.04, which is close to expectation [31]. Therefore, the mass density of the packing is ρ = φρ g = 1.47 ± 0.10 g/cm 3 . The draining angle of repose is about 24…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…In both dry and submerged cases, the grain volume fraction is measured to be φ = 0.58 ± 0.04, which is close to expectation [31]. Therefore, the mass density of the packing is ρ = φρ g = 1.47 ± 0.10 g/cm 3 . The draining angle of repose is about 24…”
Section: Methodssupporting
confidence: 68%
“…The experimental granular system consists of three sizes of technical quality glass beads (Potters Industries A-series) with material density ρ g = 2.54 ± 0.01 g/cm 3 . The grain diameter distributions are measured using a Retch Technology Camsizer.…”
Section: Methodsmentioning
confidence: 99%
“…Because of its omnipresence in industry and agriculture, one of the most widely studied systems in granular matter is the discharge of grains from a silo [1][2][3][4][5][6][7][8][9][10]. In the pioneering work of Beverloo [2] describing the mass rate Q of grains of size d flowing through an orifice of diameter D under the influence of gravity g, it was found that Q = Cρ b √ g(D − κd) 5/2 , where ρ b is the apparent density of the material and C and κ are constants related to the particle nature and silo geometry.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most relevant aspects of these expressions is the independence of Q on the column height, in contrast to the hydrostatic dependence at the bottom of a water column. Recently, it has been also investigated the granular discharge of submerged hoppers, and a surge in the flow rate was measured at the end of the process [5]. A granular material is usually defined as a conglomerate of macroscopic particles characterized by a loose of energy due to elasticity and friction when particles collide or slide [6].…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Wilson et al [1] describes experimental results on the discharge of hoppers filled with granular material and immersed in water. The discharge of dry granular matter through hoppers (as well as pipes and silos of various geometries) has been -and is still -much studied, due to the practical importance of these flow geometries but also because of the theoretical difficulties posed by their puzzling behavior.…”
Section: Introductionmentioning
confidence: 99%